Die Christen en die owerheid volgens Romeine 13:1–7 - Pelser, G. M. M. (Hervormde teologiese studies, 1986)
The Christian and the ruling authorities according to Romans 13:1–7 In this article the question is posed as to the appropriate understanding and applicability of Romans 13:1–7 in modern times and modem political situations, especially in the light of world wide revolutionary tendencies and activities. First the most crucial exegetical questions inherent in and attached to the passage in the history of exegesis are examined and commented on. The conclusion arrived at, is that although the passage as a self-contained unit stands somewhat loose from its paraenetical context and has its parallels in Jewish-Hellenistic thought, there is no reason to minimise the thrust of its admonition to subjection to ruling authorities. This cannot be done either on the grounds that the passage is non-Pauline or on the grounds of metaphysical, historico-political or eschatological considerations. Regarding the understanding and applicability of the passage in our present situation, the conclusion is that the Christian at least should always adhere to the main purport of the passage, but not necessarily unqualified. Because the passage stands hermeneutically in a dialectical relationship to every new situation, it should be treated in a responsible way in such new situation without, however, either letting the situation prescribe the exegesis or letting the passage enforce itself as dogma upon the situation.